Effect of Surface Properties on the Photo-Induced Crawling Motion of Azobenzene Crystals on Glass Surfaces - Norikane, Yasuo; Hayashino, Masaru; Ohnuma, Mio; Abe, Koji; Kikkawa, Yoshihiro; Saito, Koichiro; Manabe, Kengo; Miyake, Koji; Nakano, Miki; Takada, Naoki (Frontiers in Chemistry, 2021)
Photo-induced crawling motion of a crystal of 3,3’-dimethylazobenzene (DMAB) on a glass substrate having different surface properties was studied. When exposed to UV and visible lights simultaneously from different directions, crystals crawl continuously on a glass surface. On a hydrophilic surface, the crystals crawled faster than those on other surfaces but crystals showed spreading while they moved. On hydrophobic surfaces, on the other hand, the crystals showed little shape change and slower crawling motion. The contact angles of the liquid phase of DMAB on surface modified glass substrates showed positive correlation with the water contact angles. The interaction of melted azobenzene with glass surfaces plays an important role for the crawling motion. We proposed models to explain the asymmetric condition that leads to the directional motion. Specifically by considering the penetration length of UV and visible light sources, it was successfully shown that the depth of light penetration is different at the position of a crystal. This creates a non-equilibrium condition where melting and crystallization are predominant in the same crystal.